The Analysis Study of Prevalence, Management and Outcome of Thalassemia in Children : A Comprehensive Systematic Review - Irwanto, Muhammad; Khoirunnida; Istiningtyas, Kartika (International Medical Journal Corp. Ltd, 2024)
Background: Thalassemia is an inherited autosomal recessive disease resulting from mutations in the α- and β-globin gene clusters on chromosome 16 and chromosome 11, respectively. The aim of this study to show about prevalence, management and outcome of thalassemia in children. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The prevalence and gene mutation spectrum of thalassemia display obviously heterogeneity among children. The findings provide the valuable information for premarital and pre-pregnancy screening, prenatal diagnostic services, and designing appropriate prevention programs to control thalassemia for future.